The effects of football juggling learning on executive function and brain functional connectivity - Dong, Xiaoxiao; Gui, Xiang; Klich, Sebastian; Zhu, Lina; Chen, Dandan; Sun, Zhiyuan; Shi, Yifan; Chen, Aiguo (Frontiers in Human Neuroscience, 2024)
This study aimed to explore the relationship between motor skill learning and executive function (EF), with emphasis on the potential effects of football juggling learning. A randomized controlled trial involving 111 participants aged 17-19 was conducted. Participants were randomly assigned to either the football juggling learning (FJL) group or a control group. The FJL group underwent 70 sessions of football juggling learning, while the control group engaged in their normal daily life without an exercise intervention over the same time frame. Both groups were assessed for EF performance and underwent functional magnetic resonance imaging (fMRI) scans before and after the experiment. The executive function test included three tasks: inhibition, working memory, and shifting. The results showed significant improvement in inhibition and shifting in both groups and the FJL group showed greater improvement in these aspects of EF compared to the control group. Additionally, in comparison to the control group, the FJL group exhibited increased functional connectivity within the frontal, temporal, and cerebellar regions from pre-test to post-test. Notably, enhanced functional connectivity between the right superior temporal gyrus (posterior division) and left cerebellum 6 was identified in the FJL group and was associated with improved EF performance induced by football juggling learning. These findings shed light on the potential causal relationship between motor skill learning, EF, and brain plasticity. Importantly, our study provides preliminary evidence supporting the use of motor skill learning, such as football juggling, as a potential avenue for cognitive enhancement.